Association between triglyceride-glucose index and its combination with obesity indicators and depression: findings from NHANES 2005–2020 - Sun, Hongli; He, Wei; Bu, Jingyu; Zhang, Huifang; Huang, Huimei; Ma, Kai (Frontiers in Psychiatry, 2025)
BackgroundThe relationship between the triglyceride-glucose (TyG) index, its combination with obesity indicators, and depression remains understudied in the American population.MethodsThis cross-sectional study analyzed data from 10,423 adults in the National Health and Nutrition Examination Survey (NHANES) conducted between 2005 and 2020. We employed multivariable logistic regression analysis, smoothing techniques, generalized additive models, stratified analyses, and sensitivity analyses to examine the relationship between TyG, its combination (TyG-WC, TyG-WHtR, TyG-BMI) with obesity indicators, and depression.ResultsThe results indicate that the TyG index, TyG-WC, TyG-WHtR, TyG-BMI, and depression exhibited a significant statistical association with depressive symptoms (all P for trend < 0.001). Specifically, a one-unit increase in the TyG index correlated with a 37% increase in the risk of depressive symptoms (95% CI: 1.21–1.55), a one-unit increase in TyG-WC correlated with a 3.26 times increase in the risk of depressive symptoms (95% CI: 2.22–4.80), a one-unit increase in TyG-WHtR correlated with a 27% increase in the risk of depressive symptoms (95% CI: 1.18–1.36), and a one-unit increase in TyG-BMI correlated with a 2.30 times increase in the risk of depressive symptoms (95% CI: 1.72–3.08). There was a significant nonlinear correlation between TyG-WC, TyG-WHtR, and TyG-BMI with depressive symptoms (all P for nonlinearity < 0.001), except for a linear correlation between the TyG index and depressive symptoms (P for linearity < 0.001).ConclusionMonitoring the TyG index, TyG-WC, TyG-WHtR, TyG-BMI may facilitate depression risk assessment and prevention.